2011
DOI: 10.1186/1617-9625-9-12
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, white blood cell counts, and TNF system activity in Japanese male subjects with normal glucose tolerance

Abstract: BackgroundCigarette smokers have increased white blood cell (WBC) counts and the activation of tumor necrosis factor (TNF). The effect of smoking on WBC counts and TNF system activity, however, has not been separately investigated yet.Subjects and MethodsOne hundred and forty-two Japanese male subjects with normal glucose tolerance were recruited. They were stratified into two groups based on the questionnaire for smoking: one with current smokers (n = 48) and the other with current non-smokers (n = 94). Where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
3
12
0
1
Order By: Relevance
“…Most of these studies have employed DLC and the study subjects were mild to moderate smokers. An increase in WBC count in light smokers has also been reported previously [25]. Moreover, in the present study we have reported significance levels in WBC subsets based on absolute counts.…”
Section: Discussionsupporting
confidence: 91%
“…Most of these studies have employed DLC and the study subjects were mild to moderate smokers. An increase in WBC count in light smokers has also been reported previously [25]. Moreover, in the present study we have reported significance levels in WBC subsets based on absolute counts.…”
Section: Discussionsupporting
confidence: 91%
“…In rats of group 5, there was a diffuse expression along the alveolar walls. Watanabe et al19 reported that smoke has pro-inflammatory effects and stimulates TNF-α release by alveolar macrophages and possibly by pulmonary alveolar cells. The smoke-induced activation of TNF-α secretion usually requires a significant amount of smoke exposure 19.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al19 reported that smoke has pro-inflammatory effects and stimulates TNF-α release by alveolar macrophages and possibly by pulmonary alveolar cells. The smoke-induced activation of TNF-α secretion usually requires a significant amount of smoke exposure 19. This is consistent with the reports made by Zoppini et al20 who showed markedly increased levels of TNF-α in response to increased or long-term cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking habits were fixed based on questioner for smoking history on the value of Brinkman index. There were two groups of the smoker, the participants with Brinkman index ≥ 600 classified into heavy smoking, <600 as light smoking [21]. The categorization on smoking habit was calculated by the interviewer as the number of cigarettes inhaled since the first time of smoking by the participants.…”
Section: Samplingmentioning
confidence: 99%